Pengaruh Penggunaan Video Animasi Terhadap Pengenalan Ekspresi Anak di Taman Kanak-Kanak Sabbihisma 2 Ulak Karang - Novita Ramanda RKT; Vivi Anggraini (LPPM Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
The introduction of expressions for early childhood needs to be done, because the child's mood will greatly affect the learning process and of course it is closely related to children's learning outcomes. This research was conducted with the aim of knowing how much influence the use of animation media has on the recognition of children's expressions in group B at Sabbihisma 2 Ulak Karang Kindergarten. This type of research is a quantitative research with an experimental method with a one group pre-test post-test design model. Data collection techniques in the form of tests, observations, and documentation. The population in this study were all students of Kindergarten Sabbihisma 2 Ulak Karang, with a total of 66 students, the sample in this study were 18 children, 9 children in class B2 and 9 children in class B3. The data analysis used is the normality test, homogeneity, t-test, and also the effect size. The results showed that the experimental class using animation media obtained an average value of 17.56 while in the control class using emoticon card media it was 15.56. Thus the animation media has a significant influence on the recognition of children's expressions in Sabbihisma 2 Ulak Karang Kindergarten